Currency boards as an economic stabilization tool: How they work and where they are adopted - Antonio Cappiello (Quaderni di Studi Europei, 2006)
In recent times, interest in currency boards has come back into vogue as a tool to stabilize the nominal exchange rate and accelerate the process of economic stabilization. The most important reasons for the renewed interest in currency boards must be found in the need to face the persistent inflation of some Latin American countries as well as in the need to adopt a financial system that guarantees stability for countries in transition. Furthermore, currency boards, effectively replacing the residual autonomous monetary functions of the central bank, could represent a radical solution for a country that is lagging behind in the process of European monetary unification. At this point the question arises whether currency boards have ensured greater credibility and under what conditions. In response to these questions in the following paragraphs, after having analysed the characteristics of currency boards, we will briefly illustrate the origins of the currency board system, and then focus in more depth on the recent experience of the Argentine currency board operating from 1991 to 2002, and on currency boards currently operating in Bosnia and Herzegovina, Bulgaria, Estonia, Hong Kong and Lithuania; the currency boards of the latter countries will also be analysed in a comparative manner and summarized in a synoptic table. Finally, the main advantages and disadvantages of the currency board system will be illustrated in relation to the context in which they are called upon to operate.
Keywords: E00; E51; E52; 330; Currency Boards; Monetary economics